Cyclophosphamide-Induced Lipid Peroxidation and Changes in Cholesterol Content: Protective Role of Reduced Glutathione: Cyclophosphamide induced lipid peroxidation - Supratim Ray,; Subrata Chakraborty,; Bibhas Pandit,; Sumit Das, (Iranian Journal of Pharmaceutical Sciences, 2011)
The study was designed with an aim to evaluate the protective effects of reduced glutathione on cyclophosphamide induced lipid peroxidation and also changes in cholesterol content. Goat liver and white New Zealand rabbit were used as lipid source for the models. Lipid peroxidation study was performed by measuring the malondialdehyde, 4-hydroxy-2-nonenal, reduced glutathione and nitric oxide content of tissue homogenates or rabbit blood.In the cholesterol profile total cholesterol and high density lipoprotein cholesterol content of rabbit blood was determined. The data presented in this work demonstrate the lipid peroxidation induction potential of cyclophosphamide and the antiperoxidative potential of reduced glutathione on cyclophosphamide-induced lipid peroxidation. It was also observed that reduced glutathione has protective effect on cyclophosphamide-induced changes in cholesterol content. A significant correlation was also found between malondialdehyde, 4hydroxy-2-nonenal with total cholesterol as well as between reduced glutathione and nitric oxide with HDL cholesterol. These findings from both in vitro as well as in vivo models indicate the lipid peroxidation induction potential of cyclophosphamide which may be related to its toxic potential. The results also suggest the antiperoxidative effects of reduced glutathione and demonstrate its potential to reduce cyclophosphamide-induced lipid peroxidation and thus to increase therapeutic index of the drug by way of reducing toxicity that may be mediated through free radical mechanisms.